Role of teledermatology in the management of dermatological diseases among marine workers: A cross-sectional study comparing general practitioners and dermatological diagnoses - Di Canio, Marzio; Burzi, Lorenza; Ribero, Simone; Amenta, Francesco; Quaglino, Pietro (Frontiers in Medicine, 2022)
Background Diagnosis and treatment of skin disease in sea workers is an unmet need. The purpose of this study is to highlight how remote management of dermatological conditions appears inadequate in this scenario. Objective This study aimed to identify the best epidemiology for seafarers' diseases and analyze the adequacy of medical assistance in the diagnosis of dermatological maritime diseases. Material and methods A total of 420 cases of requests for dermatological diseases received by the Telemedical Maritime Assistance Service of the International Medical Radio Center (C.I.R.M.). in a referral year were included in this cross-sectional study. All pictures of cutaneous lesions had been submitted to both C.I.R.M. doctors and an expert dermatologist who provided their diagnosis. Results The most frequent diagnosis in both groups was infectious or inflammatory skin diseases. The main differences are represented by the amount of “unclassified dermatitis” or descriptive diagnosis, such as “cutaneous eruption” which were the most frequent diagnosis of C.I.R.M. doctors (p < 0.05 and p > 0.0001). In these cases, Cohen's K was <0.5 consistent with low concordance between dermatologic diagnosis and C.I.R.M. diagnosis. Conclusion and relevance Our study emphasizes the magnitude of dermatological diseases in the maritime sector, although often underestimated, and highlights the difficulty in their diagnosis for doctors on call that need more training on specific dermatological issues.